Economic Analysis of Developing Scientific Registers in African Indigenous Languages: Challenges, Opportunities, and Economic Perceptions in the Context of IsiNdebele and Natural Sciences - Fikile, Fikile (PERFECT EDUCATION FAIRY, 2024)
This interpretive qualitative case study analyzes the economic implications of developing scientific registers in African indigenous languages—specifically IsiNdebele—for natural science education. Data were collected through interviews and diary notes from stakeholders. The findings reveal that IsiNdebele remains economically underdeveloped due to the lack of scientific terminology, which limits its potential as a tool for human capital development. Stakeholders expressed divergent perceptions regarding the economic value of using a scientific register in IsiNdebele for teaching natural sciences. Some supported its use, seeing potential benefits in enhancing learning outcomes and educational efficiency through mother-tongue instruction. However, despite evidence of pedagogical benefits, many stakeholders still reject the use of a scientific register in IsiNdebele, preferring English instead. This preference is rooted in the perception of English as a global language of power and economic opportunity, considered essential for economic mobility and labor market access. Such perceptions significantly affect the economic viability of indigenous languages and hinder investments in their development. It is recommended that targeted investments be made to develop scientific registers in indigenous languages. This could shift stakeholder perceptions regarding the economic value of African languages as mediums of instruction and learning, thereby improving the economic participation of their speakers.